Pengaruh Strategi Komunikasi Pemasaran Terhadap Minat Kunjungan Wisatawan Domestik di Kabupaten Lebak (Studi Kasus Disbudpar Kabupaten Lebak) - Faujiah, Lista; Sihabudin, Ahmad; Widyastuti, Nurprapti Wahyu (Peneliti.net, 2024)
The Lebak Regency Government is trying to maximize it’s tourism potential by conducting various types of marketing communications. This is in line with the vision and mission of the Regent of Lebak who wants to make Lebak Regency a leading national tourist destination based on local potential. In the mids of budget constraints due to the Covid-19 pandemic, the government needs to know the most effective marketing communication tools to increase tourist visits in order to effectivelu use the budget. The purpose of this study was to find out the most effective marketing communication tool used by the Lebak Regency goverenment to attract domestic tourst destination in Lebak Regency. The research methode used is through path analysis testing with a cross-sectional research design on domestic tourist. From this research, it is know that the marketing communication tools that influence the interest in visiting domestic tourists are online marketing, word of mouth marketing, as well events and experiences.